The Effectiveness of PC6 Self-Acupressure on Nausea and Vomoting in Cancer Patients Undergoing Chemotherapy at Grandmed Hospital Lubuk Pakam - Cahaya Artha Anastasia Gultom; Siti Melda Lumbanraja; Widya Asa Tambunan; Lukman Sembiring, SKM, M.Kes (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Background: Chemotherapy-induced nausea and vomiting are among the most common side effects experienced by cancer patients and significantly affect their quality of life. This study aimed to analyze the effectiveness of self-acupressure at the PC6 point in reducing the severity of nausea and vomiting among patients undergoing chemotherapy at Grandmed Hospital Lubuk Pakam. A randomized controlled trial with a pretest–posttest control group design was conducted, involving 66 participants who were randomly assigned into an intervention group and a control group, each consisting of 33 respondents. The severity of nausea and vomiting was measured using the Rhodes Index for Nausea, Vomiting, and Retching. The paired data significance test used was the dependent t-test, while the comparison between groups was analyzed using the independent t-test. The results show a significant reduction in nausea and vomiting scores in the intervention group after the application of self-acupressure at the PC6 point (p = 0.001), and there is a statistically significant difference between the intervention and control groups in posttest scores (p = 0.000). These findings indicate that self-acupressure at the PC6 point is effective in reducing chemotherapy-induced nausea and vomiting and contributes to improving patient comfort and overall quality of life during treatment.